Effects of Eldoa Technique with Conservative Treatment on Pain Threshold of Active Trigger Points in Upper Trapezius and Levator Scpulae - Misbah Javaid, Haroon Mansha, Muhammad Usman Khalid, Muhammad Hassan, Yasir Kazmi, Muhammad Waseem Naseer (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The muscles that sustain body posture and the neck posture both have an impact on the cervical muscle, which is also frequently injured. The upper trapezius muscle is most frequently affected by trigger points, which is a common and prevalent condition. Aim: To assess the effectiveness of ELDOA exercises at the cervical spine and treating trigger points in the trapezius and levator scapulae. Methodology: The Ibn-e-Siena Hospital and Research Institute in Multan conducted a quasi-study. The participants were divided into two groups using a coin flip as a sampling method with the study sample size of 26. The Goniometer, Numeric Pain Rating Scale and Neck Disability Index were used to collect data from patients between the ages of 18 and 40. Results: An independent t-test was applied. Mean age ranged from 24.70±5.75 in the experiment group and 25.18±5.61 in the control group. The patients have radiated pain in control group was 3 (30%), trapezius trigger point7(70%) andlevator scapulae 3(30%) while in experimental group, pain radiating 6(60%), trapezius trigger point6(60%) and levator scapulae 4(40%). The post-results data revealed that the p values for the NPRS, Algometry and NDI significant differences were 0.025, 0.025, and 0.00, respectively. Conclusion: The results of the current investigation, the ELDOA approach considerably reduced discomfort, cervical ranges, and neck impairment brought on by trigger points. Keyword: Neck pain, Trigger Point, Skeletal Muscle, Myofascial Pain, Active Soft Tissue Release,